The association of healthy lifestyle score and risk of non-alcoholic fatty liver disease - Mitra Kazemi Jahromi; Ghazal Daftari; Hossein Farhadnejad; Asal Neshatbini Tehrani; Farshad Teymoori; Ammar Salehi-Sahlabadi; Parvin Mirmiran (BMC, 2023)
Abstract Background The combined role of important environmental factors as a single lifestyle index in predicting non-alcoholic fatty liver disease (NAFLD) risk is not fully assessed. Therefore, we aimed to investigate the association of healthy lifestyle factor score (HLS) with the odds of NAFLD in Iranian adults. Methods This case-control study was conducted on 675 participants, aged ≥ 20-60 years, including 225 new NAFLD cases and 450 controls. We measured dietary intake information using a validated food frequency questionnaire and determined diet quality based on the alternate healthy eating index-2010(AHEI-2010). The score of HLS was calculated based on four lifestyle factors, including a healthy diet, normal body weight, non-smoking, and high physical activity. An ultrasound scan of the liver was used to detect NAFLD in participants of the case group. Logistic regression models were used to determine the odds ratios(ORs) and 95% confidence interval(CI) of NAFLD across tertiles of HLS and AHEI. Results Mean ± SD age of the participants were 38.13 ± 8.85 years. The Mean ± SD HLS in the case and control groups was 1.55 ± 0.67 and 2.53 ± 0.87, respectively. Also, the Mean ± SD AHEI in the case and control groups was 48.8 ± 7.7 and 54.1 ± 8.1, respectively. Based on the age and sex-adjusted model, the odds of NAFLD were decreased across tertiles of AHEI (OR:0.18;95%CI:0.16-0.29,Ptrend<0.001) and HLS(OR:0.03;95%CI:0.01-0.05,Ptrend<0.001). Also, in the multivariable model, the odds of NAFLD were decreased across tertiles AHEI (OR:0.12;95%CI:0.06-0.24,Ptrend<0.001) and HLS(OR:0.02;95%CI:0.01-0.04,Ptrend<0.001). Conclusions Our findings reported that higher adherence to lifestyle with a higher score of HLS was associated with decreased odds of NAFLD. Also, a diet with a high AHEI score can reduce the risk of NAFLD in the adult population.